2015
DOI: 10.5146/tjpath.2014.01298
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical characteristics of cystic odontogenic lesions: a comparative study

Abstract: Objective: Cystic ameloblastoma, keratocystic odontogenic tumor, dentigerous cyst, and radicular cyst are the most commonly encountered cystic odontogenic lesions. The aim of this study was to investigate the expressions of survivin, E-cadherin, CD138, and CD38 in these lesions and their potential diagnostic usage. Material and Method:A total of 20 cases, consisting 5 radicular cysts, 5 dentigerous cysts, 5 keratocystic odontogenic tumors and 5 cystic ameloblastomas were included in our series. For all cases, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 34 publications
(65 reference statements)
1
9
0
Order By: Relevance
“…e distribution patterns of syndecan-1 in the epithelia of DC, OKC, and AB in this study were consistent with the findings of other studies [37,38,40,41]. ey were, however, unlike those ofÖzcan et al, who reported a different distribution in the OKC, describing it as a strong membranous expression in basal and suprabasal cells only, while, as in this study, it involved the full thickness of DC lining [39].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…e distribution patterns of syndecan-1 in the epithelia of DC, OKC, and AB in this study were consistent with the findings of other studies [37,38,40,41]. ey were, however, unlike those ofÖzcan et al, who reported a different distribution in the OKC, describing it as a strong membranous expression in basal and suprabasal cells only, while, as in this study, it involved the full thickness of DC lining [39].…”
Section: Discussionsupporting
confidence: 92%
“…Some biologic markers have not been investigated in the OKC yet, such as mammary serine protease inhibitor (maspin). Other markers were investigated only in a few studies, such as syndecan-1 [37][38][39][40][41].…”
Section: Introductionmentioning
confidence: 99%
“…Of these, classical cadherins are the greatest widely studied and E-cadherin belongs to the classical cadherins mediating intercellular adhesion at the level of epithelia so maintains the structural and functional integrity of epithelial tissues (14) . E-cadherin expression is inversely correlated to the grade of differentiation in different cancers (15,16). On the other hand, E-cadherin is related to aggressive cancer in many organs as, breast cancer, ovarian carcinomas, and glioblastomas, where E-cadherin is linked to decline survival and correlates with enhanced invasiveness (17)(18)(19)(20) .…”
Section: Introductionmentioning
confidence: 99%
“…In AMs and cystic lesions, the displacement of syndecan-1 from epithelium to stroma could be related to aggressiveness. [ 16 18 ]…”
Section: Resultsmentioning
confidence: 99%